2013
DOI: 10.15288/jsad.2013.74.245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Memantine on Event-Related Potential, Oscillations, and Complexity in Individuals With and Without Family Histories of Alcoholism

Abstract: ABSTRACT. Objective: Enhanced N-methyl-D-aspartate (NMDA) receptor function associated with a positive family history of alcoholism (FHP) has been hypothesized to contribute to the heritable risk for alcoholism. The objective of this study was to evaluate the relationship of alcoholism family history, NMDA receptor function, and cortical information processing by testing acute effects of the NMDA receptor antagonist memantine on event-related potential (ERP). Method: Twenty-two healthy FHP and 20 healthy famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…In line with this region-specificity, previous studies showed that large-scale impairments in brain network communication and organization is closely associated with local efficiency declines [ 44 ]. Besides, considering that the EEG-derived fractal dimension is typically inversely related to low frequency spectral power of brain activity and positively associated with power in higher frequency bands [ 12 , 45 ], fractal dimension dependence on age seems to mirror the slowing of brain activity that is shown by elderly individuals in central and parietal areas [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with this region-specificity, previous studies showed that large-scale impairments in brain network communication and organization is closely associated with local efficiency declines [ 44 ]. Besides, considering that the EEG-derived fractal dimension is typically inversely related to low frequency spectral power of brain activity and positively associated with power in higher frequency bands [ 12 , 45 ], fractal dimension dependence on age seems to mirror the slowing of brain activity that is shown by elderly individuals in central and parietal areas [ 4 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with rodent studies that showed a low dose of memantine to have minimal effect on the auditory evoked potential 36 and with human studies which showed comparable but slightly lower evoked potential under memantine treatment in healthy subjects. 37 Therefore, the memantine treatment did not affect excitability.…”
Section: Excitabilitymentioning
confidence: 95%
“…Because family history of alcoholism moderates the response to NMDA receptor antagonists (Narayanan et al, 2013; Jamadar et al, 2012: Petrakis et al, 2004), we evaluated the moderating effect of family history on the effects of memantine. Furthermore, we also explored the modulating influence of impulsivity based on emerging evidence that the NMDA system may be involved in impulsive behaviors, which may influence the decision to drink (Jentsch and Taylor, 1999; Winstanley et al 2010), and that NMDA antagonists may alter impulsive choice by increasing preference for small immediate rewards (Cottone et al 2013); while these were planned exploratory analyses we did not have a specific hypothesis about the directionality of the response.…”
Section: Introductionmentioning
confidence: 99%